PENGARUH PENGEMBANGAN KARIR DAN INSENTIF TERHADAP KINERJA KARYAWAN PT. MATAHARI DEPARTEMENT STORE JENDERAL URIP PONTIANAK - Oktaviani, Rinsan Lestari; Achmadi, Achmadi; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The .goal of thiis research wias to see how careier development and incentiives affected emplloyee performance at PT Mata.hari Departmeint Store Jenderal Uriip Pontiianak. The research approach employed is quantitative research utilizing descriptive methods."˜This study included 48 "˜employees from PT Mat.ahari Departmeint Store Jenderall Urip Pontiana"™k. I.n th"™is stiudy, question.naires and doicumentation were employeid as tihe prima.ry data gatheriing "˜methods. Multiplle linear regressiion ana"™lysis withiSPSS ve.rsion 20 was usied to analyize the data. With a Tvalue of 3.710 Ttable 2.014 aind a significance of 0.001 0.05, the findiings diemonstrated tihat caireer devellopment ha.s a positiive and subst.antial impacit on tihe "˜performance of employeies of PT Matahari Departmeint Stiore Jendeiral Uriip Pon.tianak. Wit.h a Tva"™lue of 2.661 Tta.ble 2.014 and a si"™gnificance of 0.011 0.05, incientives haive a posiitive and significiaint i mpact on empllloyee peiriformance at PT Mata.h.ari Dep.ar.tment Sto.re Jenderlal Uri.p Pontianak. Tihe performance of emplo.yees of PT. Mataha.ri Depar"™tment Store Je.nderal Urip Pontia.nak is simultalneously positi.vely and siginificantly impa"™cted by caireer development and incentives, as shown by an Fcount of 20.053 Ftable 3.28 wilth a signific.ance le"™vel of 0.000 0.05 and a coefficiient of determi.nation (R2) of 0.471, or 47.1%.